Transient Elastography in Canada: Current State and Future Directions - Mohammed Aljawad; Sanjeev Sirpal; Eric M Yoshida; Natasha Chandok (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Transient elastography (TE) is a safe and effective technology to noninvasively assess hepatic fibrosis in patients with numerous liver conditions. TE is not readily available to all Canadians, and data regarding how this technology is incorporated into clinical practice are lacking.